The habitat suitability of Timor friarbird (Philemon inornatus) in Western Timor Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Paga B, Pudyatmoko S, Wijayanti LR, Yuda P, Sulaksono N. 2021. The habitat suitability of Timor friarbird (Philemon inornatus) in Western Timor Island, Indonesia. Biodiversitas 23: 703-713. Timor friarbird is an endemic bird to Timor Island. The population of this bird has been declining due to land cover changes as a result of massive anthropogenic pressures. This study aimed to assess the suitability of Timor friarbird's habitat by using 12 ecogeographical variables. The sources of data included Sentinel 2A satellite imagery and remote sensing-based algorithms. The bird's presence was analyzed by using a combination of line transect with point count methods. Ecological Niche Factor Analysis (ENFA) model was applied to obtain habitat suitability value as well as coefficient of marginality (M) and specialization (S). These results showed that the Timor friarbird needs a habitat with a different value from the average of the entire habitat. High specialization value indicated that the species has a narrow ecological niche. Factors influencing habitat suitability included the distance from roads, the presence of mangroves, primary and secondary dryland forests, rivers, and low-density settlements. About 75% of the study area is classified as unsuitable habitat, and only 22% is suitable with range classes of suitability from marginal to optimal habitat. Areas with less anthropogenic pressure on the land cover will be preferred more by the bird. Improvement of unsuitable habitat and protection of suitable habitat, therefore, will be the most important strategy for Timor friarbird conservation.